The problems of developing a competitive national TV programs in the reality of the market relations (Herald of Journalism, 2018)
The paper is devoted to topical issues of increasing the share of domestic television content in themodern media market of Kazakhstan. The importance of creation of competitive teleproducts for attractionof a viewership and potential advertisers is noted. The tendencies of increasing the volume ofthe state information order for the development of the domestic television industry are analyzed andthe author gives a number of recommendations. Some aspects of creating TV content and changing theadvertising market in Kazakhstan in connection with the introduction of market relations on televisionhave been analyzed. The article also deals with the problems of production and broadcasting of modernKazakhstan TV. It is shown how the viewership and advertising market at this stage due to the introductionof market relations on television. Consider the value of the country’s information policy in thedevelopment of the domestic TV industry.Key words: media market, the domestic television content, the advertising market, the state informationorder.
Keywords: Key words: media market, the domestic television content, the advertising market, the state information order.